(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In this article, the author discusses “Сomparative Sufism”, which exists in the field of Sufi studies to this day, but has not yet received recognition as a methodology for studying this religious and philosophical teaching. According to the author, the first elements of “Comparative Sufi Studies” can be found in the scientific works of such theoreticians of Sufism as Hakim at-Termizi and Imam Mustamli Bukhari in the IX th -XI th centuries.